Analisis Peminatan Brevet Pajak Dengan Pilihan Berkarir Dibidang Perpajakan Sebagai Variabel Mediasi - Ristiyana, Rida; Atichasari, Anna Sofia; Herdiyanti, Nadya Dwi; Zainuddin, Zain (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
This study aims to determine the influence of the variables of career motivation, quality motivation, knowledge motivation and perception of education costs on tax brevet specialization with career choice in taxation as an intervening variable. The type of research is quantitative research using primary data through questionnaires. The research population is s1 accounting students in semesters 6 and 8 at Tangerang City University. The sampling technique used purposive sampling, with a sample of 100 respondents. The data analysis method uses partial least square using smartpls 3.0 software. The results of the study simultaneously career motivation, quality motivation, knowledge motivation and perception of education costs have an effect on tax brevet specialization. The results of the study were partially career motivation and knowledge motivation had a positive and significant effect on career choices in the field of taxation, while quality motivation and perception of education costs had no effect on career choices in the field of taxation then partially quality motivation, perception of education costs and career choices in the field of taxation had a positive and significant effect on the tax brevet specialization, while career motivation and knowledge motivation had no effect on the tax brevet specialization. The results of the mediation effect test showed that career choice in the field of taxation could mediate and strengthen career motivation and knowledge motivation for tax brevet specialization, and career choice in taxation could not mediate quality motivation and perception of education costs for tax brevet specialization.